2015
DOI: 10.1016/j.physio.2015.03.2085
|View full text |Cite
|
Sign up to set email alerts
|

Living with joint hypermobility syndrome. Patient experiences of diagnosis, referral and self-care

Abstract: Background. Musculoskeletal problems are common reasons for seeking primary health care. It has been suggested that many people with 'everyday' non-inflammatory musculoskeletal problems may have undiagnosed joint hypermobility syndrome (JHS), a complex multi-systemic condition. JHS is characterized by joint laxity, pain, fatigue and a wide range of other symptoms. Physiotherapy is usually the preferred treatment option for JHS, although diagnosis can be difficult. The lived experience of those with JHS require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 8 publications
2
33
1
2
Order By: Relevance
“…The outcome of surgical and physical therapy treatment is largely disappointing, which illustrates the need for a stronger evidence base [Rombaut et al, ]. Education for health professionals [Billings et al, ; Rombaut et al, ; Terry et al, ; Lyell et al, ; Russek et al, ] is paramount in order to optimize physical therapy provision. A recent feasibility study of a six session package of treatment demonstrates future potential [Palmer et al, ,] and further research is required to explore the specific therapeutic actions of physical therapy for managing JHS/hEDS.…”
Section: Principles Of Management Of Individuals With Jhs/eds‐ht In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of surgical and physical therapy treatment is largely disappointing, which illustrates the need for a stronger evidence base [Rombaut et al, ]. Education for health professionals [Billings et al, ; Rombaut et al, ; Terry et al, ; Lyell et al, ; Russek et al, ] is paramount in order to optimize physical therapy provision. A recent feasibility study of a six session package of treatment demonstrates future potential [Palmer et al, ,] and further research is required to explore the specific therapeutic actions of physical therapy for managing JHS/hEDS.…”
Section: Principles Of Management Of Individuals With Jhs/eds‐ht In Cmentioning
confidence: 99%
“…The reported prevalence of JHS/hEDS in adult physical therapy outpatient musculoskeletal settings has been reported to be between 30% [Connelly et al, ] and 55% [Clarke and Simmonds, ]. Despite the relatively high incidence of JHS/hEDS, recent research has found that many physical therapists and other clinicians are not familiar with the diagnostic criteria, prevalence, or common clinical presentation of affected individuals [Billings et al, ; Lyell et al, ; Russek et al, ], whereas clinicians also experience a lack of awareness of this condition [Billings et al, ; Rombaut et al, ; Terry et al, ; Lyell et al, ]. This guideline aims to provide physical therapists and other clinicians with the state of the art regarding the assessment and management of children, adolescents, and adults with JHS/hEDS.…”
Section: Introductionmentioning
confidence: 99%
“…The main purposes of treatment are symptomatic control and improvement of functional capacity. The patients should be taught to deal with the disease by modifying their activities, with self-care activities, preventing trauma by limiting the amplitude of movements, correcting posture and performing oriented physical exercise to muscle strengthening and joint stability, avoiding pain and articular wear [1][2][3]8 .These patients need to be managed for his JHS, as a multisystemic disease, and not for an individual symptom, as pain 13 . The use of analgesics and NSAIDs are generally ineffective and orthopedic surgery should be avoided 10 .…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Accordingly, patients with JH may experience frustrating delays in diagnosis or misdiagnosis, lengthy diagnostic evaluations focused on isolated symptoms, and an overall poor understanding of their disorder among clinicians. 12,16 & The Ehlers-Danlos syndromes (EDS) represent a group of quintessential inherited connective tissue disorders that characteristically include prominent JH. EDS subtypes are categorized further by their clinical features and associated genetic markers.…”
Section: Clinical Teaching Pointsmentioning
confidence: 99%